Compositional modulation and surface stability in InGaP films: Understanding and controlling surface properties - Bortoleto, J. R R [UNESP]; Gutiérrez, H. R.; Cotta, M. A.; Bettini, J. (AIP Publishing, 2007)
We investigate the formation of compositional modulation and atomic ordering in InGaP films. Such bulk properties - as well as surface morphologies - present a strong dependence on growth parameters, mainly the V/III ratio. Our results indicate the importance of surface diffusion and, particularly, surface reconstruction for these processes. Most importantly from the application point of view, we show that the compositional modulation is not necessarily coupled to the surface instabilities, so that smooth InGaP films with periodic compositional variation could be obtained. This opens a new route for the generation of templates for quantum dot positioning and three-dimensional arrays of nanostructures. © 2007 American Institute of Physics.
Keywords: Compositional modulation; Compositional variation; Surface stability; Nanostructures; Semiconducting indium compounds; Semiconductor quantum dots; Surface diffusion; Surface morphology; Surface properties; Surface reconstruction; Thin films